Technological capabilities and patterns of cooperation of UK firms: a regional investigation - Simona Iammarino; Mariacristina Piva; Marco Vivarelli; Nick von Tunzelmann (Institute for the Study of Labor (IZA), 2009)
This paper focuses on the relationship between firms' technological capabilities and different forms of cooperation for innovation by combining the analysis of both micro and meso levels, i.e. the level of the firm and of the geographical region. Our findings, based on the Fourth UK Community Innovation Survey (CIS), provide new insights regarding the relationship between cooperative linkages for innovation and the development of technological capabilities by business units. Firstly, the distinction between competences and capabilities adopted in this paper seems appropriate for going beyond the rather simplistic dichotomy of 'innovative' versus 'non-innovative' firms commonly used in interpreting CIS data. Secondly, we find that the analysis for the UK as a whole masks stark regional differences in terms of intra- and extra-region collaborative linkages and degrees of firms' technological capabilities. These findings may be useful to help policy making to meet the priorities highlighted within the UK Government's framework for Science & Technology.
urn:nbn:de:101:1-20090513272
Keywords: O30; R12; 330; Cooperation for innovation; technological capabilities; firms; regions; Innovation; Unternehmenskooperation; Forschungskooperation; Technologie; Kernkompetenz; Region; Großbritannien